2011
DOI: 10.1586/erm.11.44
|View full text |Cite
|
Sign up to set email alerts
|

Bone disease in multiple myeloma and precursor disease: novel diagnostic approaches and implications on clinical management

Abstract: The manifestations of bone involvement in patients with multiple myeloma (MM) can have devastating clinical effects and increase mortality. Recent studies demonstrate that patients with the precursor conditions smoldering MM (SMM) and monoclonal gammopathy of undetermined significance (MGUS) show evidence of bone disease and increased risk of fractures. The understanding of the pathogenesis of bone disease in MM has expanded in recent years. The traditional skeletal survey will probably be replaced by newer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…2 Patients with MM have a high incidence of bone disease, including osteopenia, osteolytic lesions, and fractures, which can significantly increase morbidity and mortality in patients with MM. 3 We previously performed a population-based study of 5326 MGUS patients diagnosed in Sweden, compared with 20 161 matched controls, and observed a 1.6-fold significantly increased risk of any fracture at 10 years' follow-up in MGUS patients. Furthermore, there was a higher risk for axial (skull, vertebral/pelvis, and sternum/costae) compared with distal (arm and leg) Submitted fractures.…”
Section: Introductionmentioning
confidence: 99%
“…2 Patients with MM have a high incidence of bone disease, including osteopenia, osteolytic lesions, and fractures, which can significantly increase morbidity and mortality in patients with MM. 3 We previously performed a population-based study of 5326 MGUS patients diagnosed in Sweden, compared with 20 161 matched controls, and observed a 1.6-fold significantly increased risk of any fracture at 10 years' follow-up in MGUS patients. Furthermore, there was a higher risk for axial (skull, vertebral/pelvis, and sternum/costae) compared with distal (arm and leg) Submitted fractures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in improving imaging techniques in MM. Features of an optimal imaging technique include high sensitivity for detecting lytic bone lesions and infiltrative focal lesions (FLs) in the bone marrow (BM), reliability in detecting extramedullary disease (EMD), and ability to assess response to treatment [1]. Low-dose computed tomography, magnetic resonance (MR), and positron emission tomography (PET) integrated with computed tomography (PET/CT) using the positron emitting radionucleotide 18F-fluorodeoxyglucose (FDG) have some of the above-mentioned characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Experimental data 3 and clinical observations 1 suggest that bone disease drives MM progression and that early changes in bone remodeling precede transformation of MM from monoclonal gammopathy of undetermined significance (MGUS), 4 a benign stage of MM. 5 Compared with control subjects, patients with MGUS have decreased bone mineral density (BMD) and cortical and trabecular thickness 6 and increased risk of fractures.…”
Section: Introductionmentioning
confidence: 99%
“…7 A population-based study showed that patients with MGUS (N 5 5326) had a 1.6-fold increased risk of any fracture at 10 years after diagnosis. 1 Because recent reports implicated CYR61 upregulation by osteoblastactivating agents, we sought to investigate its role in MM. CYR61 is a growth factor-inducible gene 8,9 that encodes a cysteine-rich, extracellular matrix-associated heparin-binding protein, CCN1.…”
Section: Introductionmentioning
confidence: 99%